2018
DOI: 10.1177/0284185118787354
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of tumor size measurement: comparison of B-mode ultrasound, strain elastography, and 2D and 3D shear wave elastography with histopathological lesion size

Abstract: Background Predicting the exact extent of a breast tumor is of great importance for oncologic treatment strategies. Different types of elastography can be used as new tools for measuring lesion size. Purpose To provide evidence regarding the accuracy of tumor size measurement of strain elastography (SE), two-dimensional (2D) and three-dimensional (3D) shear wave elastography (SWE), and conventional B-image ultrasound. Material and Methods In this prospective study, the diameter of 105 malignant breast lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Farrokh et al [ 1 ] recently reported data that proves that USWE is much more precise for measuring cancer size. Another study by Farrokh et al [ 41 ] confirmed that USWE can predict the lesion size precisely compared to other modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farrokh et al [ 1 ] recently reported data that proves that USWE is much more precise for measuring cancer size. Another study by Farrokh et al [ 41 ] confirmed that USWE can predict the lesion size precisely compared to other modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer size assessment with preoperative imaging is crucial for the staging of disease [ 1 ]. Size of the primary tumour is also a major prognostic indicator and is one of the three parameters used in the American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) cancer staging; although T does not represent the precise size of the tumour, this does indicate the location and extent of the tumour in the prostate gland.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, a correlation between breast tumor stiffness and receptor status, histological grade, and Ki-67 expression has been reported, suggesting that tumor evaluation using elastography could in future venture beyond determining whether tumors are malignant or benign (205). To this end, 3D elastography has recently become clinically available, facilitating whole tumor evaluation, which could also pave the way for more accurate tumor classifications (206).…”
Section: Elastographymentioning
confidence: 99%
“…Die 3D-SWE wurde auch für die Beurteilung der Tumorgröße bei Brustkrebs in einer aktuellen Studie verwendet [26]. Im Vergleich zur 2D-SWE, Strain-Elastografie und zum B-Mode Ultraschall war die konventionelle B-Mode Bildgebung überlegen, obwohl 3D-SWE in der Untergruppe mit invasiv-duktalem Karzinom genauer war als 2D-SWE und SE.…”
Section: Elastografie In Der Brustbildgebungunclassified
“…3D SWE has also been used for tumor size assessment in breast cancer in a recent study [26]. When compared to 2D SWE, strain elastography and B-mode ultrasound, conventional B-mode imaging was superior, although 3D SWE was more accurate than 2D SWE and SE for the subgroup of invasive ductal carcinoma.…”
mentioning
confidence: 99%